Lipid-Mediated Insertion of Toll-Like Receptor (TLR) Ligands for Facile Immune Cell Engineering - Zhang, Michael H. (Front Immunol, 2020)
Cell-based immunotherapies have tremendous potential to treat many diseases, such as activating immunity in cancer or suppressing it in autoimmune diseases. Most cell-based cancer immunotherapies in the clinic provide adjuvant signals through genetic engineering to enhance T cell functions. However, genetically encoded signals have minimal control over dosing and persist for the life of a cell lineage. These properties make it difficult to balance increasing therapeutic efficacy with reducing toxicities. Here, we demonstrated the potential of phospholipid-coupled ligands as a non-genetic system for immune cell engineering. This system provides simple, controlled, non-genetic adjuvant delivery to immune cells via lipid-mediated insertion into plasma membranes. Lipid-mediated insertion (termed depoting) successfully delivered Toll-like receptor (TLR) ligands intracellularly and onto cell surfaces of diverse immune cells. These ligands depoted into immune cells in a dose-controlled fashion and did not compete during multiplex pairwise loading. Immune cell activation could be enhanced by autocrine and paracrine mechanisms depending on the biology of the TLR ligand tested. Depoted ligands functionally persisted on plasma membranes for up to 4 days in naïve and activated T cells, enhancing their activation, proliferation, and skewing cytokine secretion. Our data showed that depoted ligands provided a persistent yet non-permanent adjuvant signal to immune cells that may minimize the intensity and duration of toxicities compared to permanent genetic delivery. Altogether, these findings demonstrate potential for lipid-mediated depoting as a universal cell engineering approach with unique, complementary advantages to other cell engineering methods.